Association of Host Pharmacodynamic Effects with Virologic Response to Peginterferon Alfa-2a/Ribavirin in Chronic Hepatitis C - Chung, Raymond T. (2010)
Patients receiving therapy for chronic hepatitis C virus (HCV) infection frequently experience cytopenias and weight loss. We retrospectively assessed the pharmacodynamic effects of peginterferon alfa-2a and ribavirin by evaluating the relationship between changes in hematologic parameters, body weight, and virologic response. Patients with HCV genotypes 1, 4, 5, or 6 receiving 24 or 48 weeks of peginterferon alfa-2a and ribavirin therapy were pooled from four phase III/IV trials. Maximum decreases in hemoglobin, neutrophils, platelets, and weight during therapy were assessed by virologic response category (sustained virologic response [SVR], relapse, breakthrough, and nonresponder) and by race/ethnicity. Of 1778 patients analyzed, more than half were male, non-Hispanic Caucasians, infected with HCV genotype 1, with baseline HCV RNA >800,000, and alanine aminotransferase ≤3 × ULN. Virologic responders (SVR, relapse, and breakthrough) experienced greater maximum decreases from baseline in neutrophils, platelets, hemoglobin, and weight compared with nonresponders; however, no clear trend was observed between SVR, relapse, and breakthrough. After adjusting for drug exposure and treatment duration, only decreases in neutrophils remained associated with virologic response. Significantly greater declines in neutrophils (P<0.0001) and platelets (P<0.005) were observed at weeks 4, 12, and 24 of therapy in virologic responders compared with nonresponders. This difference between responders and nonresponders was also observed among race/ethnic groups although statistical significance was not consistent across all groups. CONCLUSION: This post hoc analysis of HCV patients treated with peginterferon alfa-2a and ribavirin shows that maximum decreases from baseline in hematologic parameters and weight loss were associated with virologic response. However, after adjusting for drug exposure and accounting for duration of therapy, only neutropenia was independently associated with virologic response.